The Impact of Using Mobile Learning Applications on the Development of Students' Digital Literacy - Rossa Ramadhona; Schersclight Oscar; Morse Kathryn; Wolnough Cale (Yayasan Adra Karima Hubbi, 2024)
Background:The use of mobile learning applications has influenced students' digital literacy levels. The use of information technology as a learning medium, including mobile learning, can influence students' motivation to learn and make learning easier and faster. Using mobile learning applications can also increase students' digital literacy, especially in terms of connections. Research Objectives:The aims of this research are to identify the impact of using mobile learning applications on the development of students' digital literacy, assess students' abilities in using mobile learning applications, determine how the use of mobile learning applications is effective and efficient in increasing students' digital literacy, and assess the impact of using mobile learning applications on the development of digital literacy student. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From the research results, it can be seen thatMobile learning apps can help students learn more about digital literacy. This application can offer a variety of learning materials and information related to digital literacy, so that students can better understand and expand their knowledge. Conclusion:From this research, researchers can conclude that the impact of using mobile learning applications on the development of students' digital literacy can increase students' interest in learning, help them learn digital literacy and students' learning resilience.